RESPON PERTAMBAHAN DIAMETER Gyrinops caudata TERHADAP DUA KOMBINASI PUPUK - Yusak M. Dori; Marthen T. Lasut; Semuel P. Ratag (Universitas Sam Ratulangi, 2017)
ABSTRACT Gyrinops caudata an agarwood-producing plants are of good quality, so the price on the market also increased tailored to the needs of the present. To meet the demand of the market it is necessary to improve the welfare of farmers cultivation of agarwood and reduce the level of damage to forests from natural forests aloes search uncontrollably. Cultivation of this crop requires the application of techniques and methods that aim to spur growth in order to produce quality results and growth in accordance with the growing age. This study aims to investigate the response of fertilizer given to plants producing agarwood by using the experimental method, the observed data were analyzed using the F-test (variance) to determine the spread of the data and proceed to the t-test to determine the level of difference in the increase in diameter of the two group of plants. Through the analysis of test-f and proceed to the t-test concluded that the treatment that is given in plant with a combination of fertilizer, NPK and added foliar fertilizer (bayfolan) accreting diameter better than combination fertilizers that do not add foliar fertilizer Bayfolan.Key words : Agarwood, Gyrinops caudata, Fertilizers, Bayfolan, Experiment.